Determinan Transparansi Pengelolaan Laporan Keuangan Daerah Melalui E-Government Pada Pemerintah Indonesia - Ilham, Dwi Salsbila; Sfitri, Adek Wahyuni; Yahya, Khairani; Sabrina, Sarah Vika; Madi, Suka; Kasmita, Tiara (Universitas Serambi Mekkah, 2024)
In the era of regional autonomy, transparency in regional financial management is crucial to realizing accountability and public trust. E-government is very important in regional financial management because it can increase transparency, efficiency and service quality, as well as facilitate access to financial information. The results of this research indicate that local governments need to increase the use of official websites to disclose financial information and increase the transparency of regional financial management. Apart from that, regional governments also need to improve the quality of financial reports and increase community participation in regional financial management. In this way, local governments can improve transparency, efficiency and service quality, as well as facilitate access to financial information, so that the public can monitor regional financial management more easily and effectively.